If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -33 + -3x = 7x + 23 Reorder the terms: -33 + -3x = 23 + 7x Solving -33 + -3x = 23 + 7x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-7x' to each side of the equation. -33 + -3x + -7x = 23 + 7x + -7x Combine like terms: -3x + -7x = -10x -33 + -10x = 23 + 7x + -7x Combine like terms: 7x + -7x = 0 -33 + -10x = 23 + 0 -33 + -10x = 23 Add '33' to each side of the equation. -33 + 33 + -10x = 23 + 33 Combine like terms: -33 + 33 = 0 0 + -10x = 23 + 33 -10x = 23 + 33 Combine like terms: 23 + 33 = 56 -10x = 56 Divide each side by '-10'. x = -5.6 Simplifying x = -5.6
| 4=2(x) | | y=2(-1) | | 1.5(2x-6)=3 | | 6x+159=13x-9 | | 5(2x-4/5)=x-4 | | (3x+11)=(2x+48) | | 3(1x-9)=6 | | -40x-8y=8 | | 10x-15=6x-7 | | -5(8+4x)=-20 | | 5(-2+x)=-50 | | F(x)=x^3-6x^2+7x-2 | | 3(-1-5x)=117 | | 2=-12(x) | | x/2-6=2 | | a^2+4(3+5)= | | 2=-12x | | x^2-7x-11 | | a^2+4(3+9)= | | 7(2+3x)=56 | | y=-12(-3) | | q=5 | | n=12+7 | | -7(6x-2)=-28 | | -11-2y=-3 | | 3(-8+4x)=96 | | x-2(5)=-3 | | 3x–6=2x+4 | | 12y-5y=21 | | 6(5x+4)=-96 | | -14=-6+7 | | 2n+-4=n |